Monitoring Parental dan Perilaku Teman Sebaya Terhadap Perilaku Seksual Remaja SMA Di Kota Pontianak - Suwarni, Linda (Jurnal Promosi Kesehatan Indonesia, 2009)
Background: The number of unwanted pregnancy, Sexually Transmitted Disease (STDs) and HIV-AIDS among adolescents are rapidly increased nowadays. There was 10% of Pontianak adolescents engaged in premarital sexual intercourse since they were 16 or 18 years old, and most of sexual activities happened at home. This study aims to analyze the impact of parental monitoring and peer influence to adolescents’ sexual attitudes.Method: It was a cross sectional study involving 348 students from 50 high schools in Pontianak. Univariate, Bivariate and Path Analysis was used to find the correlation and the direct path of independent variable to dependent variable.Result: It was found there was a direct impact (10.6%) and indirect impact (9.28%) of parental monitoring to adolescents sexual behavior. Peer influence was shown to be the most dominant path in affecting adolescents’ sexual behaviors both direct (20.2%) and indirect (14.24%). Parental monitoring in this study was having a weaker impact to adolescents sexual behavior than did peer influence, therefore, it is necessary for parents to approach their adolescents and give them sex education in order to give them a better understanding in making sexual decisions.Keywords : Parental, Monitoring, Sexual, Behavior, Adolescent